2016
DOI: 10.5812/ircmj.19871
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Labor in Post-Term Pregnancy by Chamomile

Abstract: BackgroundPost-term pregnancy is an important factor in perinatal mortality and morbidity. Generally, to reduce perinatal mortality in pregnancy, the delivery is done before adverse perinatal morbidity occurs. To prevent prolonged pregnancy, labor is induced with chemical drugs and complementary therapies. Due to the side effects and contraindications of chemical medicine, the use of herbs has been investigated in the induction of labor in post-term pregnancy.ObjectivesThis study was done to identify the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
7
0
1
Order By: Relevance
“…Sua aplicação pode ser um risco quando associada à fármacos industrializados e preparos artesanais, havendo a probabilidade de interações medicamentosas que podem prejudicar a mãe e o feto. Como benefícios, podem ser elencados: tratamento de infecções, alivio da dor, redução dos sintomas de ansiedade e distúrbios do sono (GHOLAMI et al, 2016;PIRES;ANDRADE;OLIVEIRA, 2021).…”
Section: Resultsunclassified
“…Sua aplicação pode ser um risco quando associada à fármacos industrializados e preparos artesanais, havendo a probabilidade de interações medicamentosas que podem prejudicar a mãe e o feto. Como benefícios, podem ser elencados: tratamento de infecções, alivio da dor, redução dos sintomas de ansiedade e distúrbios do sono (GHOLAMI et al, 2016;PIRES;ANDRADE;OLIVEIRA, 2021).…”
Section: Resultsunclassified
“…Also, in a double‐blinded clinical trial by Gholami et al. ( 2016 ) on 80 post‐term pregnant women with a gestational age of 40 weeks or more, it was found that after one week of taking chamomile extract‐containing capsules, labor symptoms began to appear, and compared to the control group, labor pain and contraction duration decreased (Gholami et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that in gonadectomized mice, chamomile extract improves estrogen-dependent sexual parameters including hair growth, temperature changes, and the menstrual cycle (Kesmati et al, 2006). Also, in a double-blinded clinical trial by Gholami et al (2016) on 80 post-term pregnant women with a gestational age of 40 weeks or more, it was found that after one week of taking chamomile extract-containing capsules, labor symptoms began to appear, and compared to the control group, labor pain and contraction duration decreased (Gholami et al, 2016).…”
Section: Matricaria Chamomilla (Chamomile)mentioning
confidence: 99%
“…However, a study by Zafar et al [ 63 ] found no significant difference in pain relief during labor between women using Chamomile and women receiving Pentazocine. An Iranian study analyzed the effectiveness of chamomile in inducing labor in women with a gestational age of 40 weeks or more, cephalic presentation, an absence of uterine contraction, as well as a cervical Bishop score of less than four [ 64 ]. Women in the study group received capsules with chamomile extract (500 mg) for 7 days (6 capsules a day).…”
Section: Herbal Medicines Used To Counteract Some Pregnancy-related Symptoms (Eg Nausea and Vomiting Dizziness And Headache And Memory Lomentioning
confidence: 99%